Taxes In Islamic Law Perspectives - Raden Bambang Jaeng Rono (Proceeding International Seminar of Islamic Studies, 2019)
The majority of Indonesian people are muslim. Muslims related to wealth and income there is an obligation in the form of zakat for those who have fulfilled the requirements. As Indonesian citizens, muslims also have tax obligations for those who have fulfilled the requirements, because a law has been made that requires it.Taxes in Islamic law which are a source of state revenue are not known. Therefore, the different scholars agree on the status of tax law in terms of the concept of Islamic economics. In the concept of Islamic law tax is a liability that can be temporarily, obliged by ulil amri as dharibah, due to the lack of Baitul Mal, and can be removed if the condition of Baitul Mal has been refilled, obliged only to rich muslims, and must be used for their interests (muslims), not in the public interest, as a form of muslim jihad to prevent greater danger if that is not done. Second, there are two opinions in this regard, those who argue that tax is permissible in Islam after the obligation of zakat. Others argue that taxation is not permissible in Islam, because in Islam the obligation of a muslim in property is only on zakat.